Measurement of the longitudinal relaxation time for the nitrogen nuclear spin in a nitrogen-vacancy colour centre of diamond. (December 2021) - Soshenko, V.V.; Cojocaru, I.S.; Bolshedvorskii, S.V.; Rubinas, O.R.; Smolyaninov, A.N.; Vorobyov, V.V.; Sorokin, V.N.; Akimov, A.V.
Abstract: A longitudinal relaxation time of a nitrogen-14 atom nuclear spin for a nitrogen-vacancy (NV) colour centre in diamond is measured by the modified double optical resonance method. The diamond sample was grown by the method of high temperature and pressure and comprised 1 ppm of NVcentres. The longitudinal relaxation time was 43(6) s, which was compared to the time calculated in the model of relaxation due to the electron spin of colour centre interaction with phonons and spin reservoir. The time measured well agrees with predictions of the model.